Взаимосвязанные области по природным ресурсам в регионе ЕЭК - United Nations Economic Commission for Europe (United Nations, 2021)
This publication reviews the situation, trends, challenges and main interactions for the five natural resources of the Nexus – water, energy, food, land and materials – from the perspective of the United Nations Economic Commission for Europe (ECE) Region. Increasing demand, changing climates and technologies, growing populations and social inequalities, urbanization, globalization and other megatrends are putting pressure on natural resources in the ECE region and elsewhere. There are many complex policy issues and difficult choices to be made, necessitating a comprehensive nexus approach that can address the interactions and trade-offs involved. This is recognized at the international level where, amongst other things, the integrative character of the 2030 Agenda for Sustainable Development calls for an assessment of the linkages and complementarities but also of the possible conflicts that exist between different Sustainable Development Goals (SDGs) and targets. The Natural Resource Nexus emphasizes the need to view water, energy, food, land, and materials as complex and inter-related entities rather than as separate ones. This approach ensures more integrated and sustainable perspectives of natural resource management and use, beyond the traditional sectoral silos, that can be applied at all scales. It further provides an opportunity to identify and prioritize cross-sectoral and integrative solutions. Statistics, transport and trade, three interlinkages which are very relevant to the Nexus, are also considered here.